Sulfide precipitation of copper from alkaline glycine-cyanide solutions: Precipitate characterisation - Deng, Deng; Oraby, Elsayed; Eksteen, Jacques (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
© 2019 Elsevier Ltd A synergistic leaching system using glycine containing starvation levels of cyanide as lixiviants has been shown to be an effective approach to leach gold-copper ores, allowing the consumption of cyanide to be reduced significantly while glycine is recycled. Sulfide precipitation to remove the bulk of the copper was studied. The previous study on the precipitation behaviour of Cu and Au from the alkaline glycine-cyanide solution shows that the cupric (Cu2+) glycinate can be easily precipitated, while the gold and cuprous (Cu+) cyanide species remain stable in the solution. Due to the sparingly soluble nature of metal sulfides, colloidal and poorly settling particles are usually formed without control methods, which create challenges for solid-liquid separation processes such as thickening and filtration. This study investigated the effects of chemical and operational conditions on particle characteristics particularly particle size distributions (PSD). Settling characteristics, particle morphologies and particle structure were also studied. In the presence of divalent cations such as Ca2+ and Mg2+, particularly Ca2+, large and fast settling particle agglomerates were generated. Increasing ionic strength of the solution was also noted to enlarge the particles. The high supersaturation level has insignificant effects on the PSD as long as Ca2+ is present. A relatively large particle size is generated at a medium stirring speed with fast addition rate. There are no significant effects of aging, heating, and seeding on the PSD, but these factors profoundly influenced the morphologies of the individual particles according to the SEM results. SEM and XRD analysis illustrate that a more mature and crystalline copper sulfide precipitates were produced after aging, heating, or seeding.